PERANAN HUMAS PERUSAHAAN APLIKASI TRANSPORTASI ONLINE UBER BALI DALAM MENJAGA HUBUNGAN DENGAN DRIVER - Natalia, Natasha Fera; Pascarani, Ni Nyoman Dewi; Pradipta, Ade Devia (E-Jurnal Medium, 2018)
ABSTRACT The presence of Uber in Bali raise a controversy so that the action of rejection frequently happened such as demonstration and sweeping was done by the local transportation and conventional taxi alliance. Those action of rejection often contained a violence that cause the Uber driver feel unsafe and harmed. The Uber Bali public relation hold up the role to keep the relation with their drivers as one of the stakeholders who have an important role for the company. Therefore, the study, entitled "Peranan Humas Perusahaan Aplikasi Transportasi Online Uber Bali dalam Menjaga Hubungan dengan Driver” have a purpose to find out the role by Uber Bali public relation in order to maintain the relation with their drivers. The method applied is analysis descriptive qualitative method with qualitative research and post-positivism paradigm. The results from this research based on the role concept of public relations according to Dozier and Broom, Uber Bali’s public relation intent to hold the role as an expert presciber and communication facilitator. As an expert presciber Uber Bali try on offer to solve the problems happened whether to supervise the emergency condition from the management, stakeholders, as well as the problem appear from the area. As a communication facilitator, Uber Bali’s public relation hold a role to provide a sharing session regarding the promo or the latest regulation as well as correspondence session with the driver if theres any concern from them. Key Words: Public Relation, Uber Bali, Driver, Stakeholders